(→개요) |
(→개요) |
||
4번째 줄: | 4번째 줄: | ||
<math>\left( \frac{x+1}{x-1} \right)'</math> | <math>\left( \frac{x+1}{x-1} \right)'</math> | ||
<math>=\left\{ (x+1)(x-1)^{-1} \right\}'</math> | <math>=\left\{ (x+1)(x-1)^{-1} \right\}'</math><ref>[[곱의 미분]]</ref> | ||
<math>=(x+1)' \cdot (x-1)^{-1} + (x+1) \cdot \left\{ (x-1)^{-1} \right\}'</math> | <math>=(x+1)' \cdot (x-1)^{-1} + (x+1) \cdot \left\{ (x-1)^{-1} \right\}'</math> |
2015년 10월 18일 (일) 10:56 판
1 개요
- (x+1)/(x-1) 미분
[math]\displaystyle{ \left( \frac{x+1}{x-1} \right)' }[/math]
[math]\displaystyle{ =\left\{ (x+1)(x-1)^{-1} \right\}' }[/math][1]
[math]\displaystyle{ =(x+1)' \cdot (x-1)^{-1} + (x+1) \cdot \left\{ (x-1)^{-1} \right\}' }[/math]
[math]\displaystyle{ =\frac{ (x+1)' }{ x-1 } + (x+1) \cdot \left\{ -1 \cdot (x-1)^{-2} \right\} }[/math]
[math]\displaystyle{ =\frac{ 1 }{ x-1 } - \frac{ x+1 }{(x-1)^2} }[/math][2]
[math]\displaystyle{ =\frac{x-1-(x+1)}{(x-1)^2} }[/math]
[math]\displaystyle{ =\frac{-2}{(x-1)^2} }[/math]
2 같이 보기
3 참고 자료
편집자 Jmnote Jmnote bot
로그인하시면 댓글을 쓸 수 있습니다.